Analisis Daya Dukung Fondasi Bored Pile Pada Rumah Sakit Sultan Imanuddin Pangkalan Bun: Bearing Capacity Analysis Of Bored Pile Foundation At Sultan Imanuddin Pangkalan Bun Hospital - Tenty Tamara Andriani; Fatma Sarie; Suradji Gandi (Media Ilmiah Teknik Sipil, 2023)
This study intended to analyze the bearing capacity of single bored pile, the bearing capacity of the bored pile group, the load carried, the safety factor, and the settlement that occurs. The first calculation method is Schmertmann and Nottingham method, and the second calculation method is Meyerhof method. Based on the calculation of the bearing capacity of a single bored pile using the Schmertmann and Nottingham method obtained a value Qu = 49005,88 kN, while the Meyerhof method obtained a value Qu = 1633.71 kN. The calculation results for bearing capacity of the pile group using the Schmertmann and Nottingham method obtained a value Qg = 164169,70 kN and the Meyerhof method obtained a value Qg = 5472.93 kN. The results of the load carried by the bored pile group using Schmertmann and Nottingham method is Qi = 353.98 kN ≤ Qg = 164169.70 kN which means it’s still within safe limits. Using the Meyerhof method is Qi = 353.98 kN ≤ Qg = 5472.93 kN which means it is still within safe limits. The safety factor using the Schmertmann and Nottingham method obtained SF = 463.78 and using the Meyerhof method obtained SF = 15.46 which means it is very safe. Total settlement of a single bored pile is S = 0.0142 m ≤ 0.04 m which means it is safe. And the settlement of the bored pile group is Sg = 0.03 m ≤ 0.08 m which also means it is safe